Sales promotion in health and medicine: using incentives to stimulate patient interest and attention - James K. Elrod; John L. Fortenberry (BMC, 2020)
Abstract Background Sales promotion-the use of incentives to encourage patronage-is a staple of marketing communications in the health services industry. Sales promotion applications commonly used by health services organizations include free samples, free trials, coupons, contests, and loyalty programs. These avenues engender goodwill, appreciation, and attentiveness; they also serve as small, but powerful promotional mechanisms by reminding recipients of healthcare institutions, compelling particular actions, encouraging repeat business, or prompting some related desirable in an effort to hasten exchange and bolster loyalty. Discussion Sales promotion offers myriad opportunities for healthcare providers to connect with audiences. While limited in their power to attract broad audiences when used in isolation, sales promotion avenues used in tandem with other marketing communications create helpful engagement synergies which amplify conveyance initiatives. This article presents an overview of sales promotion and notably shares deployment insights and experiences from Willis-Knighton Health System, permitting peer healthcare establishments to view associated pathways, reflect on their own sales promotion efforts, and potentially bolster initiatives with the perspectives supplied herein. Conclusions Sales promotion offers healthcare providers a complementary communications avenue, helping to reinforce other elements of the marketing communications mix, affording opportunities to develop better connections with patients. In formulating associated communication plans, health and medical establishments should be reminded of the benefits offered by sales promotion and especially strive to effect creative applications that build interest and attention. By doing so, opportunities to bolster patient volume and increase all-important market share abound.